Philosophical foundations of language in the law - Marmor, Andrei; Soames, Scott (Oxford : Oxford University Press, 2011)
This collection brings together the best contemporary work in the area of philosophy of language and the law. The first area concerns a critical assessment of the foundational role of language in understanding the nature of law itself. The second main area concerns a number of ways in which an understanding of language can resolve some of the issues prevalent in legal interpretation, the third general topic concerns the role of language in the context of particular legal doctrines and legal solutions to practical problems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Language